Comment On Fixed and Float Exchange Rate Regimes - Anton Abdulbasah Kamil (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2007)
The theory of exchange rate regimes does not provide clear cut preference as to which regimes shouldbe preferred. Fixed and floating exchange rate regimes each has its own advantages anddisadvantages. Under fixed exchange rates, the country’s export and service sector are stable becausethe businessmen need not worry about the fluctuation of the currency, and thereby influencing theamount of profit made. Moreover, without worry about the fluctuation of the value of the currency,businessmen can make beautiful enterprise to do business. The implication is that it creates muchneededjobs and revenue for the country. In this paper we will prove theoretically that in short, fixedexchange rates can provide greater insulation of output in the face of nominal shocks. At the sametime, floating exchange rates are better at absorbing real shocks.